Pharmacologic inhibition of lysine-specific demethylase 1 as a therapeutic and immune-sensitization strategy in pediatric high-grade glioma. Issue 9 (13th March 2020) - Bailey, Cavan P; Figueroa, Mary; Gangadharan, Achintyan; Yang, Yanwen; Romero, Megan M; Kennis, Bridget A; Yadavilli, Sridevi; Henry, Verlene; Collier, Tiara; Monje, Michelle; Lee, Dean A; Wang, Linghua; et al.
Abstract: Background: Diffuse midline gliomas (DMG), including brainstem diffuse intrinsic pontine glioma (DIPG), are incurable pediatric high-grade gliomas (pHGG). Mutations in the H3 histone tail (H3.1/3.3-K27M) are a feature of DIPG, rendering them therapeutically sensitive to small-molecule inhibition of chromatin modifiers. Pharmacological inhibition of lysine-specific demethylase 1 (LSD1) is clinically relevant but has not been carefully investigated in pHGG or DIPG. Methods: Patient-derived DIPG cell lines, orthotopic mouse models, and pHGG datasets were used to evaluate effects of LSD1 inhibitors on cytotoxicity and immune gene expression. Immune cell cytotoxicity was assessed in DIPG cells pretreated with LSD1 inhibitors, and informatics platforms were used to determine immune infiltration of pHGG. Results: Selective cytotoxicity and an immunogenic gene signature were established in DIPG cell lines using clinically relevant LSD1 inhibitors. Pediatric HGG patient sequencing data demonstrated survival benefit of this LSD1-dependent gene signature. Pretreatment of DIPG with these inhibitors increased lysis by natural killer (NK) cells. Catalytic LSD1 inhibitors induced tumor regression and augmented NK cell infusion in vivo to reduce tumor burden. CIBERSORT analysis of patient data confirmed NK infiltration is beneficial to patient survival, while CD8 T cells are negatively prognostic. Catalytic LSD1 inhibitors are nonperturbing to NK cells, while scaffolding LSD1 inhibitors are toxic to NK cells and do not induce the gene signature in DIPG cells. Conclusions: LSD1 inhibition using catalytic inhibitors is selectively cytotoxic and promotes an immune gene signature that increases NK cell killing in vitro and in vivo, representing a therapeutic opportunity for pHGG. Key Points: 1. LSD1 inhibition using several clinically relevant compounds is selectively cytotoxic in DIPG and shows in vivo efficacy as a single agent. 2. An LSD1-controlled gene signature predicts survival in pHGG patients and is seen in neural tissue from LSD1 inhibitor–treated mice. 3. LSD1 inhibition enhances NK cell cytotoxicity against DIPG in vivo and in vitro with correlative genetic biomarkers.